Influence of the carboxylate anion on the CO2 absorption mechanism using based-imidazolium ionic liquids - Diana Murillo-Criado; Fernando Aguilar-Galindo; Isabel Serrano; Miguel A. Gonzalez; Emilia Tojo; Inmaculada Suárez; Baudilio Coto; Maria Jose Tenorio (Journal of CO2 Utilization)
The reduction of atmospheric carbon dioxide (CO₂) levels is contingent upon the implementation of strategies such as the curtailment of fossil fuel usage, the adoption of renewable energy sources, and the utilization of CO₂ capture and utilization technologies. Although direct air capture (DAC) presents a significant opportunity for global mitigation, industrial efforts have primarily concentrated on pre-combustion, oxyfuel, and post-combustion capture methods to enhance environmental sustainability. Nevertheless, the economic viability of CO₂ reuse remains a significant concern, and the development of innovative solutions is imperative. In this study, the influence of the carboxylate anion on CO2 absorption process using imidazolium-derived ionic liquids (ILs) is compared. 1-Butyl-3-methylimidazolium formate ([BMIm][HCOO]), 1-butyl-3-methylimidazolium acetate ([BMIm][OAc]), and 1-butyl-3-methylimidazolium propionate ([BMIm][C3H5OO]) have been analyzed. The efficacy of the capture process was assessed by quantifying the formation of an IL-CO₂ adduct using nuclear magnetic resonance (NMR) and attenuated total reflection infrared spectroscopy (ATR-IR). Furthermore, this work studies, using Density Functional Theory (DFT) and COSMO modelling, the difference in the spontaneity of the proton transfer from the cation [BMIm]+ to the carboxylate anions of the ionic liquids used in CO2 absorption process. Based on experimental and modelling data, [BMIm][OAc] was identified as the optimal IL candidate, presents a CO2 molar fraction absorbed at 30 °C and 1 bar of 0.203, compared to 0.083 for [BMIm][HCOO] and 0.190 for [BMIm][C3H5OO]. Moreover, theoretical simulations support these results with the calculation of the acid deprotonation equilibrium constants with the highest value being obtained for [BMIm][OAc].